WORKING WITH VOCABULARY CARDS IN THE CLASSROOM - Toriida, Marie Claude Martine (PUPIL: International Journal of Teaching, Education and Learning, 2018)
Vocabulary knowledge is a very important component of language proficiency and is crucial to student success in transnational university settings. This article outlines how vocabulary flashcards were used as part of a vocabulary acquisition program in English for Academic Purposes Nursing Foundation program at university in the Middle East. Best practice recommendations by Nation (2013) are outlined regarding choosing words, and making and using word cards for explicit vocabulary learning. Explanations are given on how these recommendations were put into practice in the classroom. It is hoped that the explanations provided will serve to guide interested educators in developing vocabulary acquisition program using flashcards in their classroom.